Chapter 4: Experimenting in the organisational periphery: introducing extra-curricular entrepreneurship education in traditional research universities (Edward Elgar Publishing, 2021)
The challenge research universities encounter in introducing entrepreneurship education is observable in the contrast it creates with discipline-based education. Due to the differing purposes of science and business-oriented education, universities engage in experimenting with organisational forms designed to advance entrepreneurship at their societal interfaces. To understand such experimentation, we adopted a systems-theoretical approach for analysing related administrative decision-making. Our analysis highlights differences and similarities in the temporal unfolding of such decisions at two Finnish universities. Our chapter contributes to higher education research by investigating the emergence of the entrepreneurial university via describing the managerial operations that seek to advance entrepreneurial specialisation alongside science-oriented degree programmes during the university's transformation process. We also note that universities use flexible and creative steering mechanisms rather than strengthen their hierarchical administration structures, to avoid paralysis of decision-making in the face of differing educational content expectations.